Attitude and Family Support Influenced Human Papilloma Virus Vaccination in Female Midwifery Students - Putri, Ilfinur Anissa; Handayani, Samsriyaningsih; Tjokroprawiro, Brahmana Askandar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: In 2019 there were 13,078 cases of cervical cancer in East Java, and in 2018 the prevalence reached 2.2 per 1,000 population. However, the coverage of HPV (Human Papilloma Virus) vaccination as primary prevention of cervical cancer in Indonesia is still low. The purpose of this study was to analyze the influencing factors and the most influencing factors for female midwifery students in Human Papilloma Virus vaccination. Subjects and Method: This was an observational analytic study with a cross sectional design. The study was conducted in East Java. The study population was midwifery students. A sample of 252 midwifery students in East Java was selected by consecutive sampling. The dependent variable was HPV vaccination. The independent variables are attitudes and family support. The data were collected by online questionnaire form and analyzed by a multiple logistic regression. Results: Family support increased the likelihood of HPV vaccination in midwifery students (OR= 5.03; CI = 1.83 to 13.76; p= 0.002). Conclusion: Family support increased the likelihood of HPV vaccination in midwifery students.